2007
DOI: 10.1111/j.1464-410x.2007.06937.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate comparison of partial nephrectomy and radiofrequency ablation for clinical T1a renal tumours

Abstract: or a family history of renal cell carcinoma were excluded. From July 1996 to January 2004 110 PNs were identified in our database; 37 patients who fulfilled the inclusion criteria had either open (30) or laparoscopic PN (seven) and 40 had either percutaneous (26) or laparoscopic (14) RFA. RESULTSThe mean (range) follow-up for the RFA and PN groups was 30 (18-42) and 47 (24-93) months, respectively; the respective mean tumour size was 2.41 and 2.43 cm. There was one incomplete ablation and two local recurrences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 18 publications
3
63
0
1
Order By: Relevance
“…The established ablative method for renal cell carcinomas (RCCs) is RFA, which shows comparable oncologic outcomes to partial nephrectomy with more preservation of nephron function (6)(7)(8). CA seems to offer the advantages of minimally invasive surgery with a significantly lower late complication rate than laparoscopic partial nephrectomy (2.2% vs. 16.3%, respectively) (9).…”
mentioning
confidence: 99%
“…The established ablative method for renal cell carcinomas (RCCs) is RFA, which shows comparable oncologic outcomes to partial nephrectomy with more preservation of nephron function (6)(7)(8). CA seems to offer the advantages of minimally invasive surgery with a significantly lower late complication rate than laparoscopic partial nephrectomy (2.2% vs. 16.3%, respectively) (9).…”
mentioning
confidence: 99%
“…Stern et al published in their study disease-specific survival following RFA in T1a lesions of 93.4 % with a mean followup of 30 months. This was the same outcome for tumours of the same stage treated with partial nephrectomy [37]. In a large study of 243 procedures with a mean follow-up of 27 months, Tracey et al [38] observed a 90 % 5-year recurrence-free survival in histologically proven renal cell cancer.…”
Section: Oncological Outcome Of Rfamentioning
confidence: 55%
“…There were 8 (8%) complications none of which resulted in long-term morbidity. Stern reported with a mean follow up of 30 months that RFA had the same outcome as partial nephrectomy for T1a lesions with a disease specific survival of 93.4% [32]. Levinson described over a period of at least 40 months a recurrence free survival of 90.3% in patients undergoing RFA for SRM in a single kidney [33].…”
Section: Resultsmentioning
confidence: 99%